ACOSO SEXUAL DE LAS TURISTAS MUJERES ECUATORIANAS EN LOS DESTINOS TURÍSTICOS RURALES - JIMENEZ OLAYA SHIRLEY ANAYELI (2024)
Rural tourist destinations show a worrying problem that puts the safety of tourists at risk, such as sexual harassment of women. This is considered part of gender-based violence, and can occur verbally, through “flattery” or physically in the form of non-consensual contact. The objective of this study is to investigate sexual harassment of women in rural tourist destinations, specifically in Montañita, to understand its incidence, characteristics and patterns through a literature review, in order to provide data for future research. The study with a mixed approach, is designed as a non-experimental and exploratory research, with the application of deductive and inductive methods. The population was defined by means of non-probabilistic sampling by convenience; establishing as a representative sample 200 people among Ecuadorian women tourists for the application of surveys and 1 key actor for the application of an interview. The results showed that the most prevalent sexual harassment in Montañita rural destination is verbal and physical. The findings show that these events occur daily and are perceived as natural in the community; among their effects are also fear, disgust, guilt and anger in the victims towards their aggressors.